Developing “Learn to Write Better” Application for X Grade in SMK Kreatif - Herlina, Nur; Bahtiar, Yuyun; Nur, Luluk Choirun Nisak; Afidah, Afidah (SCHOOLAR: Social and Literature Study in Education, 2024)
In English, there are four skills namely reading, writing, listening, and speaking. Speaking can be done spontaneously very different from writing which requires paying attention to grammar and others, the purpose of this study is to design an android application that can help students develop their writing skills. This study uses the research and development method with the ADDIE model to design an application called “Learn to Write Better”. This media has been validated by media validation experts and also material validation experts. Data collection instruments were carried out from the results of interviews and questioner, the results of media validation obtained a score of 96 which was categorized as very good, for material validation obtained a score of 78 with a good category and the results of the application of the media obtained a score of 89 with a very good category. Based on the above results, the researcher concludes that the “Learn to Write Better” application is feasible to use at SMK Kreatif Hasbullah Bahrul 'Ulum Jombang.